EVOLUTION OF DEPOSITIONAL ENVIRONMENTS AFTER THE END OF MESSINIAN SALINITY CRISIS IN NIJAR BASIN (SE BETIC CORDILLERA) - Bassetti M.A.; Miculan P.; Sierro F.J. (My University, 2006)
The Messinian succession is exceptionally well preserved in the intramontane sedimentary basin of Nijar in the Internal Betic Cordillera (SE Spain). Gypsum-olistostromes and large slabs of the Azagador Member are unconformably overlain by the latest Messinian sediments of the Feos Formation. These deposits, which are studied in detail in the Rambla Los Feos outcrop (basinal area), are characterized by a sedimentary cyclicity and two lithostratigraphic units can be distinguished: (1) a lower one that mainly consists of calcarenitic intervals with laminated pelites and limestone beds (2) an upper unit showing a cyclic alternation of fluvial fan deposits and lacustrine marls, that corresponds to the 'Lago-mare episode'. The sedimentary succession records very precisely the strongly fluctuating environmental conditions during the upper Messinian, as well as the paleomorphological and paleogeographical changes that are likely related to late Miocene and Pliocene tectonic uplift of the Sierra Cabrera (Betic basement). The dominant fossil content, present throughout the upper unit in the lacustrine white marls of the Feos Formation, is represented by ostracods of the Loxocorniculina djafarovi FA, an assemblage of non-marine, aquatic communities which lived in brackish-water bodies (Lago-mare fauna). Extant ostracod faunas, similar to those documented in the Messinian fossil record and characterised by Cyprideis, Tyrrhenocythere, loxoconchids and leptocytherids, occur in hypohaline water bodies, in a salinity range of approximately 5-15‰ (mesohaline water). However, the number of species of Parathetian affinity is low, as observed in other perimediterranean areas (i.e. Apennines). The marine fauna association (foraminifera) present at levels is thought to be partly reworked, even though a marine influence at the end of the Lago-mare stage is not excluded. © 2006 Elsevier B.V. All rights reserved.
Keywords: BETIC CORDILLERA; LAGO-MARE; MEDITERRANEAN; MESSINIAN; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский